PURCHASE DECISION GARUDA INDONESIA BASED ON PERFORMANCE OF SERVICE RECOVERY, E-WOM, AND BRAND IMAGE DURING PANDEMIC COVID-19 - Rachmadianti, Desy; Rudiantara, Aldhi Nugraha; Subandi; Aafiy, Luthfy Dwi; Sundari, Siti Indah; MM, Dinda Kayani Putri Bestari, SMB (CENTRAL ASIA AND THE CAUCASUS, 2022)
During the current pandemic, many economic sectors are affected, one of which is Garuda Indonesia. The problem examined in this study is whether Garuda Indonesia, through service recovery and ewom, can form a brand image that influences decisions. Purchases during the covid 19 pandemic. The variables used in this study are service recovery and E-WOM with the dependent variables being brand image and purchase decision. The sample in this study was 194 respondents who had used Garuda Indonesia Airlines services. Data analysis in this study used the help of PLS (Partial Least Square) 3.0 software. The results showed that Service Recovery and E-WOM variables had a significant direct influence on the formation of Brand Image. Furthermore, Brand Image and service recovery have a direct and significant influence on the formation of purchase decisions.